Bladder Function after Hysterectomy - Wijaya, Johanna; Tendean, Hermie; Laihad, Bismarck J (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To determine the effect of hysterectomy on bladder function pre- and post-radical hysterectomy in early stage of cervical cancer. Method: This study was a pre-post intervention study. Data were collected through questionnaires from women who had radical hysterectomy and total hysterectomy in Prof. Dr. R. D. Kandou Manado general hospital and other networking hospitals since January 1st, 2014 to November 31st, 2014. We analyzed the data using Wilcoxon and Mann-Whitney statistical test. Result: There were each 18 respondents for the radical and total hysterectomy group in Prof. Dr. R. D. Kandou general hospital and networking hospitals. The age distribution of radical hysterectomy was 41-45 years old for 44.4%. The parity was dominated by second parity for 38.8%. In pre- and post-surgery, there were significant differences for urinary incontinence disorder (p=0.003), emptying disorder (p=0.008), urinary pain (p=0.034), and total urinary disorder (p=0.001). While, between radical and total hysterectomy, there was no significant difference in bladder function (p>0.05). Conclusion: There is an association before and after surgery to urinary function. However, there is no association between the radical and total hysterectomy group. [Indones J Obstet Gynecol 2016; 4-2: 97-100] Keywords: bladder function, cervical cancer, radical hysterectomy